Kant und die Imagination der Tiere - Villinger, Rahel (Konstanz University Press, 2018)
Kant's reflections on animals open up a hitherto overlooked approach to his conception of human intuition and imagination. In her book, Rahel Villinger shows how Kant's aesthetics, epistemology, and theory of history must be reread against the background of the assumption of sensible cognition in non-rational animals. Kant as a frigid thinker of human reason, who sees in the forces of sensibility nothing but immorality and animal baseness: this prejudice is still widespread. However, sensibility for Kant is first and foremost an autonomous and independent faculty of cognition through intuition and imagination. In this way, Kant's account of sensibility differs radically from that of the rationalist school philosophy of his day and also from the newly emerging philosophy of German idealism. Furthermore, Kant thought that we need the imagination of other animals to be able to critically think our own. Therefore, an imagination of animals with Kant includes both: the notion of a superhuman power of purely sensible intuition and imagination whose singularity and immediacy reflect the perfection and infinity of divine intuition; and the specific imagination of rational animals, whose descriptive activity combines image and writing, intuition and concept, and which becomes possible only through the imagination of their prehistorical origin - their animal prototype. Kant's reflections on animals thus reveal a hidden ambiguity in his thinking of sensible nature, which lives on in the foundations of modern aesthetics, poetics, and image theory.